Piagam Madinah: Payung Masyarakat Pluralis - Sarbini, Peter Bruno (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2013)
This article discusses the role of the Constitution or the Charter of Madina, in promoting religious tolerance. The Constitution was written to foster an honest, peaceful, and cooperative political condition in a multi-religious society. Prophet Mohammed, who drafted the Constitution, underlined that human being is basically one in unity (ummatun wahidah). He had a deep respect for humanity and other religions. Diversity of religion should not become an obstacle to accept and honor the followers of other religions. The Constitution stood as a political shelter that guarantees different religions to live side by side in freedom and dignity. In this respect, the Constitution of Madina showed that Islam, from its very beginning, has promoted toleration towards other religions.